2017
DOI: 10.1002/esp.4244
|View full text |Cite
|
Sign up to set email alerts
|

Stability of supraglacial debris

Abstract: Rock debris on the surface of ablating glaciers is not static, and is often transported across the ice surface as relief evolves during melt. This supraglacial debris transport has a strong influence on the spatial distribution of melt, and is implicated in the formation of hummocky glacial topography in deglaciated terrain. Furthermore, as ice-dammed lakes and ice-cored slopes become increasingly common in deglaciating watersheds, there is rising concern about hazards to humans and infrastructure posed by mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 79 publications
(131 reference statements)
2
58
1
Order By: Relevance
“…To map the susceptibility of supraglacial debris to instability, we applied a framework for assessing slope stability and gravitational mass transport in a debris-covered ice setting proposed by Moore (2018). Application of this framework enables the identification of areas of a glacier surface which are theoretically susceptible to one or more types of debris instability, namely: (i) simple oversteepening; (ii) meltwater saturation-excess of the debris layer, and (iii) destabilization by meltwater-induced reduction of the stable repose angle.…”
Section: Debris Stability Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…To map the susceptibility of supraglacial debris to instability, we applied a framework for assessing slope stability and gravitational mass transport in a debris-covered ice setting proposed by Moore (2018). Application of this framework enables the identification of areas of a glacier surface which are theoretically susceptible to one or more types of debris instability, namely: (i) simple oversteepening; (ii) meltwater saturation-excess of the debris layer, and (iii) destabilization by meltwater-induced reduction of the stable repose angle.…”
Section: Debris Stability Mappingmentioning
confidence: 99%
“…Model input comprises surface slope angle (in degrees) and upslope contributing area (in m 2 m), which we retrieve from our SfM-DEMs, alongside estimates of h, b, and the friction coefficient, μ, for sliding along the debris-ice interface, and the saturated hydraulic conductivity, K s , of the debris (in m d -1 ). In contrast to existing studies (Moore, 2018;Nicholson et al, 2018) we used our spatially distributed maps of h and b for input to debris stability modelling. Following Barrette and FIGURE 3.…”
Section: Debris Stability Mappingmentioning
confidence: 99%
“…However, a theoretical understanding or model reproduction of the fluctuating part of the debris-thickness distribution discussed above is not available at present. A critical role of gravity-driven non-diffusive debris redistribution processes, induced by the dynamic thermokarst topography that characterises the debris-covered ablation zone, is expected in creating and maintaining the observed inhomogeneous debris distribution (Moore, 2018;Nicholson and others, 2018). A detailed characterisation of the fluctuating part of the debris distribution would be presented in a subsequent paper.…”
Section: Spatial Variability Of Debris-thicknessmentioning
confidence: 99%
“…A glacier's response to supraglacial debris is sensitive to the debris thickness and spatial distribution, which vary according to debris sources and are subsequently affected by various transport processes at the glacier surface (Moore 2018). Moore (2018) showed that supraglacial debris could be destabilized not only on oversteepened slopes, but also where the ratio of ablation rate to debris hydraulic conductivity is large. Mapping of potential instability on the debris-covered margin of Emmons Glacier identified extensive areas that could be prone to debris destabilization and local gravitational transport (Moore 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moore (2018) showed that supraglacial debris could be destabilized not only on oversteepened slopes, but also where the ratio of ablation rate to debris hydraulic conductivity is large. Mapping of potential instability on the debris-covered margin of Emmons Glacier identified extensive areas that could be prone to debris destabilization and local gravitational transport (Moore 2018). Debris thicknesses can thus vary greatly over distances as little as a few meters, making the spatial pattern of mass balance on debris-covered glaciers highly complex (Nicholson et al 2018).…”
Section: Introductionmentioning
confidence: 99%